Sosialisasi Pemberian Infrared dan Tens pada Lansia di Desa Sukasari, Serdang Bedagai - Sulaiman Sulaiman; Anggriani Anggriani; Lagut Sutandra (Jurnal Pengabdian Pada Masyarakat, 2019)
DISSEMINATION OF GIVING INFRA-RED AND TENS TO THE ELDERLY IN SUKASARI VILLAGE, SERDANG BEDAGAI. Older adults are very susceptible to health problems. These health problems are sometimes forgotten by the elderly family to take them to the nearest Elderly integrated service post. Elderly in Sukasari Village, Pegajahan Subdistrict, Serdang Bedagai Regency, which attended 72 activities, the average elderly has physical problems and needs more treatment by giving infrared and tens. In this service, the method is carried out by conducting counseling, training on the use of infrared for the elderly, cadres, and families who follow community service. Giving infrared and tens rays significantly give a very significant impact in increasing the health status of the elderly in Sukasari Village, Pegajahan District.